2008
DOI: 10.1007/s12011-008-8094-y
|View full text |Cite
|
Sign up to set email alerts
|

Increment of Iodine Content in Vegetable Plants by Applying Iodized Fertilizer and the Residual Characteristics of Iodine in Soil

Abstract: As a new attempt to control iodine deficiency disorder (IDD), we explored a method of iodine supplementation by raising the iodine content in vegetables. When grown in the soil supplemented with iodized fertilizer, the three experimental plant species (cucumber, aubergine, and radish) show increasing iodine levels in both leaf and fruit/rhizome tissues as the iodine content added in soil increases. Excessive iodine added to soil can be toxic to plants, whereas the tolerance limit to excessive iodine varies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 9 publications
3
38
1
3
Order By: Relevance
“…The iodine concentration of algae is about 1%-2% of its dry weight. Diatomite has excellent adsorption capability which enhances absorption of iodine contributes to a preferred slow releasing of iodine [20]. The iodine concentration of algal organic iodized fertilizer is about 1087 mg/g, mostly in soluble state which is highly bio-available.…”
Section: Methodsmentioning
confidence: 99%
“…The iodine concentration of algae is about 1%-2% of its dry weight. Diatomite has excellent adsorption capability which enhances absorption of iodine contributes to a preferred slow releasing of iodine [20]. The iodine concentration of algal organic iodized fertilizer is about 1087 mg/g, mostly in soluble state which is highly bio-available.…”
Section: Methodsmentioning
confidence: 99%
“…Iodine content in plants generally increases when applying iodine as iodide, iodate or other chemical forms (Weng et al, 2008b). The best results were obtained by applying iodine compounds in the nutrient solution or foliar spraying.…”
Section: Fertilization With Iodine For Biofortification In Soilless Cmentioning
confidence: 99%
“…Fertilización con yodo para la biofortificación en sistemas de cultivo sin suelo El contenido de yodo en las plantas generalmente aumenta al aplicar el yodo como yoduro, yodato u otras formas químicas (Weng et al, 2008b). Los mejores resultados se han obtenido al aplicar los compuestos de yodo en la solución nutritiva o por aspersión foliar.…”
Section: Contenido De Yodo En Las Plantasunclassified
“…Currently the study of algae fertilizer from an iodine biofortification point of view is seldom considered (Weng et al, 2014). A critical study by Weng et al (2008) indicated that grounded dry kelp mixed with lowgrade diatomite (1 : 1) appeared to be an ideal fertilizer for increasing iodine content in soil and improving iodine uptake by plants. Weng's et al (2008) study also showed that the ability of soil to conserve iodine is limited.…”
Section: Opportunity For Algae Iodine Fertilizermentioning
confidence: 99%
“…A critical study by Weng et al (2008) indicated that grounded dry kelp mixed with lowgrade diatomite (1 : 1) appeared to be an ideal fertilizer for increasing iodine content in soil and improving iodine uptake by plants. Weng's et al (2008) study also showed that the ability of soil to conserve iodine is limited. The efficiency of iodine absorption by plants needs to be considered when applying algae fertilizer with a high iodine content ( > 300 mg kg -1 ).…”
Section: Opportunity For Algae Iodine Fertilizermentioning
confidence: 99%